Influence Of Iron On Phosphate Metabolism In Cyanobacterium Nostoc Calcicola (Applied Biological Research, 2010)
The phosphate uptake, alkaline phosphates and total extractable ATP-pool  were investigated in a cyanobacterium Nostoc calcicola Breb. under iron stress conditions. The phosphate uptake was maximum in cells raised on 200 µM Fe3+ supplemented Allen and Arnon medium, whereas 150 µM Fe3+ (used for routine  culture of Nostoc calcicolas) supported lower phosphate uptake. The cells  supplemented with higher iron (300-500 µM Fe3+) depicted reduction in  phosphate uptake with maximum reduction observed in 500 µM Fe3+ supplemented cells. Similar results were observed with respect to the effect of  iron on alkaline phosphatase activity. The alkaline phosphatase activity was minimum in cells raised on medium having 500 µM Fe3+. Also, the increase in  ATPase activity showed corresponding reduction in total extractable ATP-pool.  The reduction in ATP-pool is the resultant of lower phosphate level in cells  under Fe3+ stress.
Keywords: Alkaline phosphatase; cyanobacterium; Nostoc calcicola; phosphate; ATPase